The Roles of GmERF135 in Improving Salt Tolerance and Decreasing ABA Sensitivity in Soybean - Zhao, Meng-Jie; Yin, Li-Juan; Ma, Jian; Zheng, Jia-Cheng; Wang, Yan-Xia; Lan, Jin-Hao; Fu, Jin-Dong; Chen, Ming; Xu, Zhao-Shi; Ma, You-Zhi (Frontiers in Plant Science, 2019)
Abscisic acid (ABA) mediates various abiotic stress responses, and ethylene responsive factors (ERFs) play vital role in resisting stresses, but the interaction of these molecular mechanisms remains elusive. In this study, we identified an ABA-induced soybean ERF gene GmERF135 that was highly up-regulated by ethylene (ET), drought, salt, and low temperature treatments. Subcellular localization assay showed that the GmERF135 protein was targeted to the nucleus. Promoter cis-acting elements analysis suggested that numerous potential stress responsive cis-elements were distributed in the promoter region of GmERF135, including ABA-, light-, ET-, gibberellin (GA)-, and methyl jasmonate (MeJA)-responsive elements. Overexpression of GmERF135 in Arabidopsis enhanced tolerance to drought and salt conditions. In addition, GmERF135 promoted the growth of transgenic hairy roots under salt and exogenous ABA conditions. These results suggest that soybean GmERF135 may participate in both ABA and ET signaling pathways to regulate the responses to multiple stresses.